Nanocoating-konjac application as postharvest handling to extend the shelf life of Siamese oranges - Suriati, Luh (Frontiers in Sustainable Food Systems, 2023)
Abstract: Functional beverages made from natural ingredients have recently been in great demand and become a trend because they contribute to health. The shift in food consumption patterns that accommodate various bioactive compounds with minimum calorie intake has resulted in many new beverages. One potential product is an AVG juice made from Aloe vera gel. The weakness of AVG is the bitter taste due to the aloin content, requires the addition of other ingredients such as fruits with sweet and sour tastes to cover these weaknesses and consumer acceptability can be improved. One of the potential fruits to be formulated with AVG is bignay fruit. This study aims to determine the effect proportion of bignay fruit on the acceptability of AVG juice. This study used a completely randomized design with three replications. The concentration of bignay extract (25%, 50%, 75%) at storage temperature (6±1) °C was used to observe acidity, total dissolved solids, the organoleptic test of color, viscosity taste, and overall acceptability. Observations were made on days 0, 3, 6, 9, 12 and 15. The results showed that the concentration of bignay extract affected the acceptability of the AVG juice. The best AVG juice formula is a 50 % bignay extract on storage temperature of (6±1) °C.